A simple extraction and LC‐MS/MS approach for the screening and identification of over 100 analytes in eight different matrices. Issue 3 (21st April 2014) - Montenarh, Deborah; Hopf, Markus; Warth, Stefan; Maurer, Hans H.; Schmidt, Peter; Ewald, Andreas H.
<x xml:space="preserve">Abstract</x> In the present study, a liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) multi‐analyte approach using one single work‐up approach in whole blood, plasma, serum, post‐mortem blood, liver tissue, gastric content, hair, and urine was developed for fast target screening and reliable identification of 130 analytes often requested in clinical and forensic toxicology. Samples (500 μL each) of whole blood, plasma, serum, post‐mortem blood, tissue (homogenized 1 + 4 with water), as well as 3 g of distilled gastric contents, 1 mL of urine, or 20 mg of pulverized hair were extracted at different pH values with an diethyl ether‐ethyl acetate mixture (1:1). Separation and identification were performed using LC‐QTRAP with electrospray ionization in positive mode. For identification 1 scheduled multi‐reaction‐mode (sMRM) method with 390 transitions was developed covering benzodiazepines, Z‐drugs, antidepressants, neuroleptics, opioids, new synthetic drugs, and phosphodiesterase type 5 inhibitors. For positive sMRM transitions with intensities exceeding 5000 cps, dependent scans (EPI scan collision energy, 35 eV, collision energy spread, 15 eV) were performed for library search using our in‐house library. The method was developed with respect to selectivity, matrix effects, recovery, process efficiency, limit of detection, and applicability. The simple work‐up procedure was suitable for all biosamples with exception of urine in respect to low concentrated analytes, which showed median recovery values of 59%. The method was selective for 130 analytes in all 8 biosamples. For 106 analytes, the limit of detection in whole blood, plasma, and serum was lower than the lowest therapeutic concentration listed in blood level lists. Copyright © 2014 John Wiley & Sons, Ltd.